PREGNANCY RATE FOLLOWING TRANSFER OF FROZEN BOVINE EMBRYOS ALONG WITH hCG TREATMENT - RAO, M MUTHA; UMAMAHESH, Y; BABU RAO, K (The Indian Journal of Animal Reproduction, 2023)
The present study was an attempt to test the success of undertaking mass transfer of frozenthawed bovine embryos under village conditions and to evaluate the effect of administration of hCG on pregnancy rate of recipients. A total of 31 Jersey/HF pure bred embryos frozen in 1 .4M glycerol were transferred in to synchronized recipients. The recipients were administered two doses of 25mg dinoprost trometham ine at 11 days interval. Following successful induction of estrus, they were divided into 3 groups. GroupA(n=12) cows received 2 injections of hCG at the dose rate of 1500 IU per cow on the day of estrus and again at the time of Embryo Transfer (ET). Group B (n=9) cows received a single dose of hCG at the time of ET. Group C (n=10) animals acted as control and received no treatment. In all, 34 embryos were thawed and the cryoprotectant was removed in three steps of decreasing glycerol concentrations. Of the 34 embryos thawed, 3 (8.82%) have undergone degeneration at various stages of cryodilution and were discarded. Transfer of 31 embryos resulted in a pregnancy rate of 69.2% with no-significant difference between treatment groups. It may be inferred that frozen-thawed bovine embryos produce satisfactory pregnancy rate following selective transfer into synchronized recipients under field conditions.